GAMBARAN KUALITAS HIDUP PADA PASIEN LANSIA DENGAN OSTEOARTHRITIS - DESI NURUL HASTRIALI; Arneliwati Arneliwati; Widia Lestari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Old age is a decline in health that has an impact on physical, mental, psychological, and spiritual health. One of the main problems that occur in the elderly is Osteoarthritis. Osteoarthritis is a degenerative disease (decreased function) in the joints that usually occurs in the hands, waist, and knees. The purpose of this study was to describe the quality of life in elderly patients with Osteoarthritis.This study was a quantitative study with a descriptive method. The sampling technique was purposive sampling with 77 respondents. The measuring instrument used is the WHOQOL BREF quality of life questionnaire. The analysis used is univariate analysis. The results of this study showed that most of the respondents were aged 60 years - 69 years (71.4%), female gender (80.5%), education status not in school and elementary school (26.0%), work status not working (77.9%), married (85.7%). The results of the quality of life of Osteoarthritis patients were mostly good (61.0%), the quality of life of Osteoarthritis patients was based on the category of physical health (67.5%), psychological health category (67.5%), social relationship category (61.0%), and environmental category (53.2%). Based on 4 categories of quality of life of Osteoarthritis patients who are already good, namely monitoring of the disease and adherence to treatment. There are 2 categories of quality of life of Osteoarthritis patients that must be improved, namely social and environmental relationships of Osteoarthritis patients.Keywords: Quality of Life;Elderly; Osteoarthritis